Pentingnya Budaya dalam Bimbingan Konseling Islam bagi Remaja - Viva Justicia Foreva; Sari Dusni (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2021)
Talking about teenagers is always interesting, from the point of view of biological, psychological, social and spiritual conditions. For spiritual conditions, adolescents are in a critical condition of thinking about religious activities, so they always want the effects of religious practices to get a sense of security. Therefore, what are the ways and experiences that teenagers must have in order to be able to adapt in changing situations or very diverse cultures. Adolescent adaptability is needed in order to remain independent and ready to face the future that has been planned (even the demands of the family and the environment). Guidance and counseling with a cultural approach of "diversity or diversity in diversity" provides opportunities for adolescents to have resilience (flexibility) in facing life conditions in the 21st century which are full of very fast changes and demands for perfection in a practical way. Thus, teenagers with various uniqueness and demands of the socio-cultural environment will survive and become strong teenagers to excel in various aspects of life in continuing the ideals of family, nation and religion.